Benefits of Import of Vehicles From The Indonesia Under Decree-Law No. 30/2011: A Literature Review - Moses Cardoso (CV. Ulil Albab Corp, 2024)
The import of vehicles from Indonesia has a great significance to the sectors that involved in the tourism industry, trade and industry in Timor-Leste. The Ministry of Tourism, Commerce and Industry has the responsibility to ensure that this import benefits the country and contributes to economic development in Timor-Leste. One of the roles of the Ministry of Tourism, Commerce and Industry is related to the implementation of Decree-Law No. 30 / 2011 of 27 July. The decree-law contains the rules and regulations for the activity of import of vehicles. In this study, will be using analytical approach to analyze the impactof vehicle imports from Indonesia to the sectors of tourism, trade and industry in Timor-Leste. In addition, will conduct a study on a coasts that involved in the import, impact on the local market, competition with local products and other benefits that may result from the import of the vehicle. The nature of research in this study is qualitative with the data analysis model based on interactive model through data collection, reduction, analysis and conclusion. As a result of this research, the role of the Ministry of Tourism, Commerce and Industry is crucial to ensure the import of all vehicles from Indonesia to Timor-Leste through Dec. Law no. 30 / 2011. The import of vehicles from Indonesia has an important role to have a positive impact on the tourism, trade and industry sectors in Timor-Leste. The Ministry of Tourism, Commerce and Industry ensures the quality of vehicles imported from Indonesia in order to contribute to the economic development of the country. The guarantee is made through the implementation and assurance of the Dec. Law no. 30 / 2011 in the import process.